Outcome of Bubble CPAP in Neonate with Respiratory Distress - Afrin, Sabrina; Shirin, Mahfuza; Ahmed, Farid; Al Mamun, Mohammad Abdullah (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Continuous Positive Airway Pressure (CPAP) is a well-established mode of respiratory support in newborns. Bubble CPAP (bCPAP) is safe, efficacious and easy to use in preterm and term neonates with mild to moderate respiratory distress. Objectives: To find out the outcome of bCPAP in neonate with respiratory distress. Methods: This cross sectional study was conducted over 6 months in Bangladesh Shishu Hospital & Institute. Total 108 term and preterm neonates were enrolled who were presented with respiratory distress. Neonate with type II respiratory failure, congenital heart disease and structural malformations of lung and GI tract causing respiratory distress at birth and neonate needed intubatuin at birth were excluded. Detailed information were obtained in each case. Thorough clinical examinations were done. Relevant investigation reports were collected. All the information were recorded. Statistical analysis was done by using SPSS version 23. Results: In this study the mean age was found 43.3±43.1 hours with range from 2 to 204 hours. Majority 62(57.4%) patients were male and male female ratio was 1.3:1. Two third (66.7%) patients had birth weight ³2500 gm, 14(12.9%) had <1499 gm and 22(20.4%) patients had birth weight 1500-2499 gm. Majority (59.3%) patients belonged to gestational age between 37-41 wks, followed by 27(25%) belonged between 33-36 wks and 17(15.7%) belonged between 28-32 wks. Among the enrolled cases 18(16.7%) were RDS, 18(16.7%) were PNA, 14(13%) were PPHN, 9(4.3%) were MAS, 6(5.6%) were TTN, 13(12%) were congenital Pneumonia, 15(13.9%) were Pneumonia, 10(9.3%) were Sepsis and 5(4.6%) were Laryngomalacia. Among 108 patients who were put on bCPAP, 85(78.7%) patients were weaned and 23 (21.3%) were failed and needed mechanical ventilation. Out of 85 weaned patients hundred percent were survived and got discharge. Out of 23 failed cases 16(69.6%) cases were died and 7 (30.4%) cases were survived and got discharge. Conclusion: It is concluded from this study that bCPAP is an effective way of management of neonates with respiratory distress due to various causes. Patients who were failed in bCPAP, died more in final outcome. DS (Child) H J 2021; 38(1): 27-33